Minocycline Attenuates Sevoflurane-Induced Postoperative Cognitive Dysfunction in Aged Mice by Suppressing Hippocampal Apoptosis and the Notch Signaling Pathway-Mediated Neuroinflammation - Junjie Liang; Shanshan Han; Chao Ye; Haimeng Zhu; Jiajun Wu; Yunjuan Nie; Gaoshang Chai; Peng Zhao; Dengxin Zhang (Brain Sciences, 2023)
Postoperative cognitive dysfunction (POCD), an important postoperative neurological complication, is very common and has an elevated incidence in elderly patients. Sevoflurane, an inhaled anesthetic, has been demonstrated to be associated with POCD in both clinical and animal studies. However, how to prevent POCD remains unclear. Minocycline, a commonly used antibiotic can cross the blood-brain barrier and exert an inhibitory effect on inflammation in the central nervous system. The present work aimed to examine the protective effect and mechanism of minocycline on sevoflurane-induced POCD in aged mice. We found that 3% sevoflurane administered 2 h a day for 3 consecutive days led to cognitive impairment in aged animals. Further investigation revealed that sevoflurane impaired synapse plasticity by causing apoptosis and neuroinflammation and thus induced cognitive dysfunction. However, minocycline pretreatment (50 mg/kg, i.p, 1 h prior to sevoflurane exposure) significantly attenuated learning and memory impairments associated with sevoflurane in aged animals by suppressing apoptosis and neuroinflammation. Moreover, a mechanistic analysis showed that minocycline suppressed sevoflurane-triggered neuroinflammation by inhibiting Notch signaling. Similar results were also obtained in vitro. Collectively, these findings suggested minocycline may be an effective drug for the prevention of sevoflurane-induced POCD in elderly patients.